Situación del egresado en la especialidad de psicología de la Pontificia Universidad Católica del Perú 1962-1982 - Flor Arbulú, Marcia De la (1985)
A survey was applied to subjects that had concluded their studies in psychology in a university of Lima. The results make rvident that educational institutions are the main work source for psychologists even though the majority of them have a dcfinite clinical background.